Navigating a climate of administrative burden: the perspectives of young adult undocumented immigrants in applying for COVID-19 disaster relief assistance for immigrants in California - Ling, Irving C.; Choi, Hye Young; Sudhinaraset, May (Frontiers in Public Health, 2024)
Undocumented immigrants experienced high levels of economic insecurity during the COVID-19 pandemic while being excluded from government-based relief and unemployment benefits. In April 2020, California became the first state to offer financial aid to undocumented immigrants through the innovative Disaster Relief Assistance for Immigrants (DRAI) program in collaboration with several community-based organizations (CBOs). However, the process of applying for aid was marked by many implementation challenges, such as intake and language access; however, little data exists on the direct experiences of the undocumented community. This qualitative study examines the experiences of undocumented Asian and Latinx young adults living in California in applying for DRAI through framework of administrative burden. Themes distilled from participant experiences highlight how administrative burden via learning, psychological, and compliance costs shape the ways in which undocumented immigrants navigate policies and programs, such as DRAI. These experiences highlight the need for policymakers to address structural and programmatic administrative burdens in policy development; failure to do so result in detrimental impacts that outweigh financial benefits or cause communities to forgo needed resources.